2018
DOI: 10.1002/ams2.338
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of stroke mimics in the emergency department

Abstract: AimTo clarify the features of stroke mimics.MethodsWe retrospectively investigated stroke mimic cases among the suspected stroke cases examined at our emergency department, over the past 9 years, during the tissue‐type plasminogen activator treatment time window.ResultsOf 1,557 suspected acute stroke cases examined at the emergency department, 137 (8.8%) were stroke mimics. The most common causes were symptomatic epilepsy (28 cases, 20.4%), neuropathy‐like symptoms (21 cases, 15.3%), and hypoglycemia (15 cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 21 publications
2
23
1
3
Order By: Relevance
“…It is evident that the reliability of clinical history of an abrupt onset of focal or global neurological deficits such as hemiplegia, seen in more than half of the SM in this current study has its limitations. Some reports indicate that certain clinical features are highly suggestive of a SM and should be factored in when evaluating a suspected stroke patient [3,15]. Such factors include the paucity or absence of modifiable risk factors for stroke in clinical history [3].…”
Section: Discussionmentioning
confidence: 99%
“…It is evident that the reliability of clinical history of an abrupt onset of focal or global neurological deficits such as hemiplegia, seen in more than half of the SM in this current study has its limitations. Some reports indicate that certain clinical features are highly suggestive of a SM and should be factored in when evaluating a suspected stroke patient [3,15]. Such factors include the paucity or absence of modifiable risk factors for stroke in clinical history [3].…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20] Other studies reported other distinguishing factors that predicted SM like systolic blood pressure ≤140 mmHg, diabetes, no history of arrhythmia, altered level of consciousness, and normal ocular movements. 21,22 The brain attack study showed that SM could be predicted by changes in higher mental functions, clinical signs in other systems, ability to determine exact time of symptoms onset, unequivocal focal neurological symptoms or signs, and presence of lateralizing signs. 7 In our study, neurological symptoms did not differ between SM and real strokes, except that speech and language impairment was less common in patients with SM.…”
Section: Disclosurementioning
confidence: 99%
“…These common causes, among many others, have been reported previously. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Gibson et al 15 conducted a systematic review of 29 studies that included 8,839 patients, 25% were diagnosed with SM. The five most frequent SM in this analysis were seizure, syncope, sepsis, migraine, and brain tumors.…”
Section: Disclosurementioning
confidence: 99%
“…Stroke mimics account for 20%–25% of suspected stroke cases in the UK and 8.8% of cases in Japan . Though the common correct diagnoses were different among reports, brain tumors account for a considerable proportion of stroke mimics (Table ).…”
Section: Discussionmentioning
confidence: 99%